PENERAPAN PERENCANAAN PAJAK (TAX PLANNING) PAJAK PENGHASILAN PASAL 21 DENGAN GROSS UP METHOD - Ririn Irmadariyani (STIE Mandala Jember, 2012)
Company tax subjects are taxed on their income and have to pay to the Tax Office (Kantor Kas Negara) baed on the tax regulation. Some companies would consider corporate income tax as a burden so that they would try to pay their tax as minimum as possible as long as allowed by law and tax regulation. Therefor, companies making tax planning as a starting point in tax management. One of method in corporate income tax planning article 21 is the gross up method. By this method, income tax article 21 paid by the permanent employees will be the same amount as the tax allowance given by the employer. This tax Allowance could be considered as a company's expense that could be deducted from the company's net income and at the end it will reduce the corporate income tax paid by the company.